Tunable bioactivity and mechanics of collagen-based tissue engineering constructs: A comparison of EDC-NHS, genipin and TG2 crosslinkers. (September 2020) - Nair, Malavika; Johal, Ramneek K.; Hamaia, Samir W.; Best, Serena M.; Cameron, Ruth E.
Abstract: Due to its ubiquity and versatility in the human body, collagen is an ideal base material for tissue-engineering constructs. Chemical crosslinking treatments allow precise control of the biochemical and mechanical properties through macromolecular modifications to the structure of collagen. In this work, three key facets regarding the collagen crosslinking process are explored. Firstly, a comparison is drawn between the carbodiimide-succinimide (EDC-NHS) system and two emerging crosslinkers utilising alternate chemistries: genipin and tissue transglutaminase (TG2). By characterising the chemical changes upon treatment, the effect of EDC-NHS, genipin and TG2 crosslinking mechanisms on the chemical structure of collagen, and thus the mechanical properties conferred to the substrate is explored. Secondly, the relative importance of mechanical and biochemical cues on cellular phenomena are investigated, including cell viability, integrin-specific attachment, spreading and proliferation. Here, we observe that for human dermal fibroblasts, long-term, stable proliferation is preconditioned by the availability of suitable binding sites, irrespective of the substrate modulus post-crosslinking. Finally, as seen in the graphical abstract we show that by choosing the appropriate crosslinker chemistries, a materials selection map can be drawn for collagen films, encompassing both a range of tensile modulus and fibroblast proliferation which can be modified independently. Thus, in addition to a range of parameters that can be modified in collagen constructs, we demonstrate a route to obtaining tunable bioactivity and mechanics in collagen constructs is uncovered, that is exclusively driven by the crosslinking process. Graphical abstract: Image 1